Why do institutional investors chase return trends? - Altı, Aydoğan; Kaniel, Ron; Yoeli, Uzi (Journal of Financial Intermediation, 2012)
We propose and test a simple explanation for institutional investors’ tendency to chase return trends. When investors face uncertainty about the precision of their private information, they wait for subsequent confirming news before establishing stock positions. While such news impact the stock price, at the same time they increase investors’ estimates of the precision of their information. With low information quality the latter effect dominates and causes investors to purchase the stock after confirming good news. We formalize these ideas in a simple model and test the model’s predictions on mutual funds’ stock holdings data. Using mutual funds’ past return experiences with individual stocks as a proxy for their stock-specific information quality, we find evidence for the prediction that trend chasing is more likely when information quality is low.